Experimental and Theoretical Study of the Thermal Shock Behavior of Insulating Refractory Materials - Anabella Mocciaro; Ricardo Anaya; María Florencia Hernández; Diego Richard; Nicolás Maximiliano Rendtorff (Ceramics)
This study investigates the thermal shock behavior of three Al2O3-SiO2 commercial insulating refractory materials (JM23, JM26, and JM28) used in high-temperature industries (>1000 °C). Thermal shock resistance was evaluated through experimental tests and compared with theoretical parameters (R, R⁗, Rst) based on thermoelastic and thermomechanical models. The tests revealed that JM23 did not withstand thermal shock due to its fragility when in contact with water at room temperature, resulting in its immediate collapse. In contrast, JM26 and JM28 maintained their mechanical strength after several thermal shock cycles, although JM28 experienced a more significant decrease in compressive strength. The mechanical behavior under compression changed from semi-fragile to apparently plastic after severe heat treatments. Porosity analysis showed that JM26 had a lower pore size distribution, which contributed to its better thermal shock performance. Theoretical parameters were calculated, confirming that JM26 exhibited the highest resistance to thermal shock. These findings suggest that controlled porosity and microstructure are key factors in improving the thermal performance and durability of insulating refractory materials in high-temperature applications.